Understanding of the Accountant's Code of Ethics and Ethical Behavior of Accounting Students - Inon Listyorini; Ehrmann Suhartono; Taufik Bin Abad (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2022)
This research aims to describe the understanding of the accounting profession code of ethics, ethical behavior, and the influence of understanding the accounting profession code of ethics on the ethical behavior of accounting students. The research was conducted by survey method, with respondents as many as 59 students who had taken Basic Auditing courses. Descriptive statistics describe a much lower ethical behavior score than the average response score to all aspects of the accountant profession's code of conduct understanding. Regression testing results show that understanding the accounting profession's code of ethics positively affects students' ethical behavior. Of the five aspects of the accounting profession code of ethics, objectivity and professional behavior positively impact students' ethical behavior.